Assessment of a multiperiod optimal power flow for power system operation (2020)
The optimal power flow is an important tool for power system planning and power system operation. The optimal power flow is used in a 24-hour period to find an economic dispatch of generating units considering network restrictions. The optimal power flow provides valuable information about the operation cost, transmission flows, generation and congestion in the system. This information is used by generators, planners, operators and regulators to analyze and take decisions about the system at short and long term. At short term corresponds to information for the operation. At long term corresponds to information for the planning. This paper proposes a detailed optimal power flow formulation looking for a minimum cost of generation considering wind generation. Five solvers were used in order to compare differences between them. The solvers used are CBC, CLP, CPLEX, Gurobi and GLPK. These solvers are commonly used to solve the multiperiod DC optimal power flow. An IEEE-24 test system is used to compare the solutions provided by the solvers. The findings reveal significant differences between the solvers when they are used to solve the IEEE-24 test system. Additionally, the computing time for each solver is reported. The solvers CPLEX y Gurobi exhibits the lower computational time to find a solution